Can QuickBrain MRI replace CT as first‐line imaging for select pediatric head trauma?. Issue 5 (4th June 2020) - Sheridan, David C.; Pettersson, David; Newgard, Craig D.; Selden, Nathan R.; Jafri, Mubeen A.; Lin, Amber; Rowell, Susan; Hansen, Matthew L.
Abstract: Objective: The current standard of care for initial neuroimaging in injured pediatric patients suspected of having traumatic brain injury is computed tomography (CT) that carries risks associated with radiation exposure. The primary objective of this trial was to evaluate the ability of a QuickBrain MRI (qbMRI) protocol to detect clinically important traumatic brain injuries in the emergency department (ED). The secondary objective of this trial was to compare qbMRI to CT in identifying radiographic traumatic brain injury. Methods: This was a prospective study of trauma patients less than 15 years of age with suspected traumatic brain injury at a level 1 pediatric trauma center in Portland, Oregon between August 2017 and March 2019. All patients in whom a head CT was deemed clinically necessary were approached for enrollment to also obtain a qbMRI in the acute setting. Clinically important traumatic brain injury was defined as the need for neurological surgery procedure, intubation, pediatric intensive care unit stay greater than 24 hours, a total hospital length of stay greater than 48 hours, or death. Results: A total of 73 patients underwent both CT and qbMRI. The median age was 4 years (interquartile range [IQR] = 1–10 years). Twenty‐two patients (30%) of patients had a clinically important traumatic brain injury, and of those, there were 2 deaths (9.1%). QbMRI acquisition time had a median of 4 minutes and 52 seconds (IQR = 3 minutes 49 seconds–5 minutes 47 seconds). QbMRI had sensitivity for detecting clinically important traumatic brain injury of 95% (95% confidence interval [CI] = 77%–99%). For any radiographic injury, qbMRI had a sensitivity of 89% (95% CI = 78%–94%). Conclusion: Our results suggest that qbMRI has good sensitivity to detect clinically important traumatic brain injuries. Further multi‐institutional, prospective trials are warranted to either support or refute these findings.